94. Electromyographic correlates of paratonia. Issue 4 (April 2016) - Marinelli, L.; Mori, L.; Pardini, M.; Abbruzzese, G.; Trompetto, C.
Abstract : Paratonia can be defined as the inability of relaxing limb muscles during passive mobilization. It is divided into facilitatory paratonia, when the subject facilitates the examiner's movements, and oppositional paratonia, when the subject resists to the examiner's movements. Both types of paratonia may coexist and they have been related to cognitive impairment and frontal lobe dysfunction. Even if paratonia is frequently encountered in clinical practice, very few studies have been published, and its pathogenesis is still unknown. Measuring this phenomenon is difficult and semi-quantitative clinical scales only are available. We propose an innovative method to measure both facilitatory and oppositional paratonia: the examiner performs metronome-synchronized continuous or discontinuous movements with the patient's elbow joint, while angle and flexors/extensors EMG activity is recorded. EMG activity during passive movements could be recorded in a group of patients with paratonia assessed by clinical examination. Such EMG activity is prevalent in elbow flexors and appears both during flexion end extension movements. Continuous alternating elbow movements increase the EMG bursts amplitude and duration compared to discontinuous movements. Such EMG activity is probably the neurophysiologic equivalent of paratonia and allows a quantitative measure and distinction between facilitatory and oppositional paratonia.